Long-term evolution of a magnetic massive merger product - Schneider, Fabian; Ohlmann, Sebastian T.; Podsiadlowski, Philipp; Röpke, Friedrich; Balbus, Steven A.; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. About 10 per cent of stars more massive than ${≈}1.5\, M_{\odot }$ have strong, large-scale surface magnetic fields and are being di
Gesehen am 10.08.2020